Continuing education under Portuguese language teachers' view: limits and perspectives - Juliana Cláudia Amorim; Marcia Regina Sambugari (Universidade Federal de Santa Catarina, 2019)
This article deals with continuing education in the view of teachers of Portuguese Language, focusing on the limits, perspectives and training needs. It assumes that, in practice, continuing education courses are still shaped with a view of the teacher as the object, not the subject. Teachers participate very little in the process and maybe that is why they do not take ownership of the learning. In a qualitative approach, the data were collected through interviews with six teachers of Portuguese Language from the 6th to the 9th grades of Elementary School from different schools in the municipal school system of Corumbá City/MS. The results of this study pointed to the need of giving voice to teachers so that continuing education can reflect the image of these eyes: as a space for reflection, listening and learning.